2014
DOI: 10.1108/jfmpc-02-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Private equity investment and real estate development

Abstract: Purpose – The purpose of this paper is to understand the trends and contribution of private equity (PE) investors in real estate development in India because the real estate sector in India had witnessed significant investments from PE firms in recent years. Design/methodology/approach – The study focused on residential segment of real estate development, as it is the largest among all the segments. Two types of analyses have been done i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Similarly, Filotto et al (2018) used quarterly data ranges from 2007 to 2015 to reveal that residential mortgages loans (RMI) and HPI established a positive significant relationship with GDP while shock on GDP has a negative persistent effect on the HPI of 16 European markets. Additionally, Annamalai et al (2014) reveal that region with high growth in HPI and CPI in India tends to have greater private equity investment projects while Cheng et al (2019) established negative relationship between HPI and waiting time.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, Filotto et al (2018) used quarterly data ranges from 2007 to 2015 to reveal that residential mortgages loans (RMI) and HPI established a positive significant relationship with GDP while shock on GDP has a negative persistent effect on the HPI of 16 European markets. Additionally, Annamalai et al (2014) reveal that region with high growth in HPI and CPI in India tends to have greater private equity investment projects while Cheng et al (2019) established negative relationship between HPI and waiting time.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 93%
“…Despite, there are mixed findings on real estate pricing in general; some studies reveal that pricing behaviour is asymmetric (Annamalai et al , 2014; Cheng et al , 2019; Filotto et al , 2018), some studies found symmetric pricing behaviour of Covid-19 pandemic shock is also assumed to be an obstruction to the global economy which may be driven the negative expectation of investors’ income on HPI and could be further explained by rockets and feathers effects in support of the uneven movement of pricing behaviour. Obviously, series of studies investigated HPI from different perspectives due to undisputable contributions of real estate sector to the growth and development of national economy in particular and global economy in general (Annamalai et al , 2014; Apergis, 2015; Barros et al , 2012; Jadevicius and Gool, 2020; Mosquera et al , 2020; Tanrivermiş, 2020) and changes in the housing market could be dramatically observed (Kaya et al , 2019). Furthermore, findings on housing pricing behaviour remain inconclusive, therefore, related studies on asymmetric and symmetric of real estate pricing level discussed in the next two subsequent sections.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The real estate developers face the financial challenge at multiple phases. It starts from financial support for land acquisition, financial support for project development, financial support for construction and finally needs financial support for sales and marketing (Annamalai, Bansal & Gemson, 2014) [1]. The constraints of funding institutions like commercial banks and external borrowings motivate real estate developers to look for alternative source of financing.…”
Section: Developers Perspectivementioning
confidence: 99%